Description of two new nematode species: Ingenia major sp. nov. (Tripyloididae) and Linhystera filiformis sp. nov. (Xyalidae) from an intertidal beach of the Yellow China Sea - Yanwei, Lv; Wen, Guo; Mengna, Wang (Zootaxa, 2024)
Two new free-living nematode species, Ingenia major sp. nov. and Linhystera filiformis sp. nov., are described from the Yellow China Sea. Ingenia major sp. nov. is characterized by a large body size, six outer labial setae articulated, buccal cavity barrel-shaped with three teeth, amphidial fovea small and unispiral, spicules thin and almost straight with a pair of ventro-laterally directed teeth hooked distally, gubernaculum kidney-shaped with triangular cuticularized projection, tail conical and with swollen-terminus. Relationship between Ingenia and Bathylaimus is discussed, and Ingenia communis Gagarin & Thanh, 2007 is transferred as Bathylaimus communis comb. n. based on the buccal cavity shape. Linhystera filiformis sp. nov. is characterized by filiform body, buccal cavity minute and slit-like, six outer labial setae and four cephalic setae in the same circle and with the same length, amphidial fovea relatively small and circular, spicules short and sickle-shaped, gubernaculum boat-shaped, tail filiform with three terminal setae. An identification key for valid species of Linhystera is also given.